Performance test of oceanic wave power generator with pendulum system - Ilmi, Achmad Zidan Bahrul; Mulyono, Mulyono; Sofi’i, Yepy Komaril (Journal of Energy, Mechanical, Material, and Manufacturing Engineering, 2024)
A plentiful oceanic wave leads to the utilization of this energy into electricity. An oceanic wave power generator with a pendulum system is one of the innovations that can generate electricity from the ocean. This research aimed to identify the energy from the oceanic wave power generator with a pendulum system. It was conducted by experimenting with the pendulum rod that spins the gearbox in the generator. It was intended to measure the obtained electric power by variating the pendulum mass with the average oceanic wave speed. The research finding shows that the generator results in a maximum of 33 watts of electric power, while the lowest power is 9 watts with a pendulum mass of 0,6 kg.